Pelatihan Tenaga Medis melalui Aplikasi MCU Digital untuk Daya Saing Klinik Mutiara 1 Bekasi - Iin Iin; Ahmad Nurkamali; Dewi Kurniasari Kurniasari; Tiara Nurhayati Nurhayati (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Digital transformation in healthcare services has become a strategic requirement for clinics to improve service quality and competitiveness. One service that requires integrated management is Medical Check Up (MCU), as it involves multiple service units and produces sensitive medical record data. Klinik Mutiara 1 Kota Bekasi previously managed MCU services using manual and fragmented procedures, resulting in low service efficiency and delays in report generation. This community service program aims to enhance the competence of medical personnel and administrative staff through training and mentoring in the use of a digital MCU application. The methods applied include partner needs analysis, system development and deployment, and intensive assistance conducted over eight weeks. The results indicate that all medical personnel and staff are able to operate the digital MCU application according to their respective roles. The implementation of the system improves the efficiency of MCU service workflows, ensures more orderly management of medical record data, and accelerates the reporting process. These findings demonstrate that IPTEKS-based training and digital system implementation play an important role in improving service quality and strengthening clinic competitiveness.